Teachers' Efforts to Improve Pedagogic Competency in Learning Children with Special Needs in Inclusion Basic Schools in Surakarta - Muna, Aulia Nailul; Sunardi, Sunardi; Widyastono, Herry (The Center for Disability Studies and Services Brawijaya University, 2021)
The purpose of this study was to determine the efforts of teachers to improve teacher pedagogical competence in the learning of children with special needs in the inclusive city of Surakarta. The subjects of this study were a class teacher and a subject teacher in ten inclusive schools in the city of Surakarta. This study uses a qualitative case study method, with data collection using interview techniques from aspects of pedadogic competencies and documents of children with special needs as individual teaching programs then technical data analysis using descriptive analysis. The results of this study that based on teaching experience and educational background, teachers still need to increase efforts to improve pedagogical competence in the learning of children with special needs in inclusive schools